2020
DOI: 10.1038/s41598-020-61123-x
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for characterizing risk of type 2 diabetes mellitus in a rural Chinese population: the Henan Rural Cohort Study

Abstract: With the development of data mining, machine learning offers opportunities to improve discrimination by analyzing complex interactions among massive variables. To test the ability of machine learning algorithms for predicting risk of type 2 diabetes mellitus (T2DM) in a rural Chinese population, we focus on a total of 36,652 eligible participants from the Henan Rural Cohort Study. Risk assessment models for T2DM were developed using six machine learning algorithms, including logistic regression (LR), classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 46 publications
10
70
0
1
Order By: Relevance
“…Notably, the three serum lipid parameters showed no collinearity. The findings indicated that the GBM classifier could predict the incidence of dyslipidaemia better, which was confirmed in our previous study [ 35 ]. This might be because the GBM classifier could address the intricate relationship between predictors and dyslipidaemia.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, the three serum lipid parameters showed no collinearity. The findings indicated that the GBM classifier could predict the incidence of dyslipidaemia better, which was confirmed in our previous study [ 35 ]. This might be because the GBM classifier could address the intricate relationship between predictors and dyslipidaemia.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, the three serum lipid parameters showed no collinearity. The ndings indicated that the GBM classi er could predict the incidence of dyslipidaemia better, which was con rmed in our previous study [35]. This might be because the GBM classi er could address the intricate relationship between predictors and dyslipidaemia.…”
Section: Discussionsupporting
confidence: 81%
“…What is noteworthy is that the three serum lipid parameters showed no collinearity. The ndings pointed out that GBM classi er could predict the incidence of dyslipidemia better, which had been con rmed in the previous study [30]. This might be due to the GBM classi er could deal with the intricate relationship between predictors and dyslipidemia.…”
Section: Discussionsupporting
confidence: 70%